1994
DOI: 10.1126/science.7997877
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Control and Cancer

Abstract: Multiple genetic changes occur during the evolution of normal cells into cancer cells. This evolution is facilitated in cancer cells by loss of fidelity in the processes that replicate, repair, and segregate the genome. Recent advances in our understanding of the cell cycle reveal how fidelity is normally achieved by the coordinated activity of cyclin-dependent kinases, checkpoint controls, and repair pathways and how this fidelity can be abrogated by specific genetic changes. These insights suggest molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
1,359
1
37

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,292 publications
(1,418 citation statements)
references
References 131 publications
21
1,359
1
37
Order By: Relevance
“…25,26 In particular, increasing evidence has clearly demonstrated that cancer transformation is due to the loss of function of specific tumor suppressor genes (Rb, p53, and p16 genes) controlling the cell division cycle in many tumors. 27 Tumors with chromosomal translocation, which is considered a main genetic lesion for the tumor, are often accompanied by additional aberration of tumor suppressor gene(s). 28,29 In our present study, a subset of acute leukemias with MLL gene rearrangement demonstrated homozygous deletion of p16 and p15 genes.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In particular, increasing evidence has clearly demonstrated that cancer transformation is due to the loss of function of specific tumor suppressor genes (Rb, p53, and p16 genes) controlling the cell division cycle in many tumors. 27 Tumors with chromosomal translocation, which is considered a main genetic lesion for the tumor, are often accompanied by additional aberration of tumor suppressor gene(s). 28,29 In our present study, a subset of acute leukemias with MLL gene rearrangement demonstrated homozygous deletion of p16 and p15 genes.…”
Section: Discussionmentioning
confidence: 99%
“…All of these lesions have been shown to block transcription in vivo and in vitro, and to be implicated in signaling cell cycle arrest and apoptosis (Kulms and Schwarz, 2002). Cell survival after DNA damage is dependent on two important biological responses: the activation of cell cycle checkpoints and of DNA repair machinery (Hartwell and Kastan, 1994).…”
Section: Cell Cycle Checkpointsmentioning
confidence: 99%
“…In an individual, however, if either of these processes is not regulated properly, the cell number can increase inappropriately to cause tumour formation (Hartwell and Kastan, 1994). During apoptosis, cells die by following an ordered intracellular mechanism in which proteins and DNA are degraded.…”
Section: Introductionmentioning
confidence: 99%